Life Insurance Aggregate Claims Distribution Model Estimation - Yohandoko, Setyo; Prabowo, Agung; Yakubu, Usman Abbas; Wang, Chun (Operations Research: International Conference Series, 2023)
Risk is a hazard or consequence that can occur in an ongoing process or future events. As the party responsible for assuming and managing risks, the insurance company must be prepared to provide compensation in the event of claims; otherwise, they may face bankruptcy. Hence, it is important to understand the characteristics of risks handled by the insurance company. The risk's characteristics can be analyzed through the distribution model of previous-period claims. The sum of aggregate claims over several periods forms the aggregate claims distribution. The aggregate claims distribution used to determine the amount of pure premium and gross premium that must be obtained by the insurance company. In this research, the determination of distribution model estimation was examined for data cases on aggregate claims of life insurance in Indonesia 2016-2020. The result of this research conduct that the appropriate distribution model is the inverse Gaussian 3P distribution (three parameters).